People on the Move | Environmental Migrants - Dave Dalton (United States Heinemann Educational Books, 2006)
Your environment is everything around you buildings, land, water, air, living things, and other people. It looks pretty solid and settled, but it is always changing.
Keywords: No Poverty; Global Issues -- Global Issues; Environment Issues -- Environment Issues; Migration -- Migration